(3efgGL GdHjGf ajeG jSJYedg GdGfSGf ef GdGOhjI GdeaQOI hGdeQcHIs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s ((3CUHgGf s)
(3ChdgG (B:s
(3GdMeO ddg GdPj XgQJ HOGFg eUfhYGJg hQJHJg Ydi MQha GdeYLe hfebJg Ydi GdhLg GdeMQQ GdeMce aHOCJ HGdCda s
(3BNQgG (B:s
(3jfJhf gh GdKGajSG Cj UeZ GdSPGH GdLHdj s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs